Solution‐Processed Pure Sulfide Cu2(Zn0.6Cd0.4)SnS4 Solar Cells with Efficiency 10.8% Using Ultrathin CuO Intermediate Layer. Issue 9 (5th August 2020) - Zhuk, Siarhei; Wong, Terence Kin Shun; Petrović, Miloš; Kymakis, Emmanuel; Hadke, Shreyash Sudhakar; Lie, Stener; Wong, Lydia Helena; Sonar, Prashant; Dey, Avishek; Krishnamurthy, Satheesh; Dalapati, Goutam Kumar
Abstract : Herein, it is demonstrated that incorporating ultrathin p‐type cupric oxide (CuO) enhances the performance and stability of solution‐processed Cu2 (Zn0.6 Cd0.4 )SnS4 (CZCTS)/CdS thin film solar cells. In sol–gel CZCTS/CdS thin film solar cells, nanoscale CuO films (4–32 nm) are deposited on top of molybdenum (Mo) by magnetron sputtering and this is used as an intermediate layer (IL). The CuO IL thickness has a significant effect on the short‐circuit current density ( J SC ) in CZCTS/CdS solar cell devices. As a result, a maximum power conversion efficiency (PCE) of 10.77% is measured for the optimized device with 4 nm CuO compared with 10.03% for the reference device without a CuO layer. Furthermore, the stability of the devices is enhanced significantly by incorporating the CuO IL. This work demonstrates that through proper design of the CuO IL thickness, both the back interface quality and optical property of the CZCTS absorber can be tuned to enhance the device performance. Abstract : Incorporating ultrathin p‐type cupric oxide (CuO) enhances the performance and stability of solution‐processed Cu2 (Zn0.6 Cd0.4 )SnS4 (CZCTS)/CdS thin film solar cells. The CuO intermediate layer (IL) thickness has a significant effect on the short‐circuit current density ( J SC ). A maximum power conversion efficiency (PCE) of 10.77% is measured for the device with 4 nm CuO compared with 10.03% for the reference device without a CuO layer.